Maintenance engineering handbook - Mobley (New York :: McGraw-Hill Education, 2014)
"Updated, modernized, digitized, and streamlined edition of this classic handbook which has been educating plant and facility professionals in every aspect of maintenance engineering for more than half a century"--
Includes index.
Includes bibliographical references and index.
Keywords: Plant maintenance -- Handbooks, manuals, etc; TECHNOLOGY & ENGINEERING / Engineering (General)